Product Innovation Rahn Tasjily Based on Sharia Agrowisata (Rahn Agrowisata) - Arman Rajiman; Nazlida Muhammad; Irvan Iswandi (Mabahits Al-Uqud, 2024)
Rahn Tasjily is an innovative Islamic financing solution that provides financial solutions based on fixed asset collateral, such as land certificates, where the collateral remains in the possession of the rahin (borrower) and can be utilized by them. This product is highly relevant in supporting the development of the Islamic agro-tourism sector, which integrates environmental sustainability values and promotes community-based economic empowerment. Through the Rahn Tasjily mechanism, rural communities can access financing to develop halal agritourism businesses, such as Sharia-compliant homestays, halal restaurants, organic farm tours, and educational gardens, without compromising control over their assets. This study aims to analyze the implementation of Rahn Tasjily at PT Pegadaian Syariah, the challenges encountered, and its potential to support maqashid sharia. Using a normative research method, the analysis reveals that Rahn Tasjily is not only relevant to enhancing Islamic financial inclusion but also to sustainably promoting rural economic empowerment. However, its successful implementation requires the support of more specific regulations, public education, and the development of rural infrastructure.